WORLD POLITICS: A NONLINEAR ANALYSIS - Bafoev , Feruz Murtazoevich (Innovative Development in Educational Activities, 2023)
The article describes world politics through the method of non-linear analysis, discusses the advantages and disadvantages of this research method.